Temperature dependent impedance spectroscopy of (Co3O4)x/CuTl-1223 nanoparticles-superconductor composites. Issue 4 (March 2018) - Mumtaz, M.; Naveed, M.; Amin, Badshah; Imran, M.; Khan, M. Nasir
Abstract: Cobalt oxide (Co3 O4 ) nanoparticles and Cu0.5 Tl0.5 Ba2 Ca2 Cu3 O10-δ (CuTl-1223) superconducting phase were prepared by sol-gel and solid-state reaction methods, respectively. Co3 O4 nanoparticles were added in CuTl-1223 superconducting matrix to get (Co3 O4 )x /CuTl-1223; x = 0–2.0 wt% composites. Different experimental techniques like X-ray diffraction, dc-resistivity measurements and complex impedance spectroscopy were used for characterization of these composites. Crystal structure of CuTl-1223 superconducting phase remained unchanged after addition of Co3 O4 nanoparticles, which suggested that these nanoparticles were settled at grain-boundaries. Superconducting transport properties were decreased after inclusion of Co3 O4 nanoparticles. Role of Co3 O4 nanoparticles addition at the grain-boundaries of the host CuTl-1223 phase was investigated and overall decreasing trend was observed in both real and imaginary part of impedance. The decrease in blocking factor by varying the content of Co3 O4 nanoparticles is the evidence of increase in conductivity of grain-boundaries. The impedance master curves indicated the temperature independent dynamic process with non-Debye type relaxation phenomenon. The temperature dependent ac-conductivity with increasing contents of these Co3 O4 nanoparticles was also investigated and increasing trend was observed.